APLIKASI ASUHAN KEPERAWATAN GENERALIS DAN PSIKORELIGIUS PADA KLIEN GANGGUAN SENSORI PERSEPSI: HALUSINASI PENGLIHATAN DAN PENDENGARAN - Irma Erviana; Giur Hargiana (Institute Teknologi dan Kesehatan (ITEKES) Bali, 2018)
Hallucinations are the most common problems in nursing diagnoses of mental disordes. Hallucinations are the distortions of false perceptions that occur in maladaptive neurobiological responses. Hallucinations usually appear in patients with mental disorders the result of the change in reality orientation, patients feel the stimulation that actually does not exist. In this profession program the author has the opportunity to manage directly, by providing nursing care and analyzing the final results that will be documented in the form of final scientific work ners. The care of nursing for a client a of sensory perception disorder: sight and hearing hallucinations that is a symptom of an early psychosis, the majority of this case which happened in the end of adolescenceor early adulthood , confuse is the role which have affect to the fragile personality disorder so that there is the disorder of self-concept and pulling themselves from a social environment that gradually get the teenager become too deep in fantasy and cause the emergence of hallucinations. The nursing process is performed based on generalist nursing care standard for 9 days of hospitalization, Started from the date of 2 and 10 of May 2018. Theobtained results are the main nursing problems which is perception sensory disorder: hallucinations.The Implementations that focus on controlling hallucinatory efforts by rebuking and also modalities of therapy: psychoreligious. The nursing order that is provided give good results to the clients on the mark by no longer hearing the voices that often mock clients and the diminishing intensity of dajjal’s presence that be seen by the clients.